Triazolinedione-"clicked" poly(phosphoester)s: systematic adjustment of thermal properties. Issue 28 (29th June 2017) - Becker, Greta; Vlaminck, Laetitia; Velencoso, Maria M.; Du Prez, Filip E.; Wurm, Frederik R.
Abstract : The thermal properties of halogen-free flame retardant poly(phosphoester)s from acyclic diene metathesis polycondensation have been optimized by a systematic post-modification using 1, 2, 4-triazoline-3, 5-dione derivatives. Abstract : The thermal properties of halogen-free flame retardant poly(phosphoester)s from acyclic diene metathesis polycondensation have been optimized by a systematic post-modification using 1, 2, 4-triazoline-3, 5-dione derivatives. The straightforward modification not only increased their glass transition temperatures significantly but also improved the thermal stability with respect to their char yields.